Análise da execução de ações de eficiência energética nas instalações elétricas da sede centro da UTFPR em Curitiba - Mokwa, Ramires Herrmann (2021)
An energy efficiency project was executed out at the Federal Technological University of Paraná (UTFPR) Central Headquarter’s between the years 2019 and 2020. This project was approved by the Companhia Paranaense de Energia (COPEL) through the Public Call COPEL 001/2017 and contemplates the replacement of 12,133 common lamps per led lamps and the installation of a Grid-Connected Photovoltaic Power System (SFVCR) of 95.04 kWp of power. The COPEL invested financial resources, through contracts and protocols of technical cooperation entered into with UTFPR, in an energy efficiency project and in a research and development project (P&D), the latter with objectives of encouraging completion works, dissertations, research projects, scientific initiations and technological development of projects. As of incentives sundry, such as those of the P&D project, it was possible to analyze the global efficiency of UTFPR Central Headquarters’ electrical installations through the comparisons of electric energy consumptions previous and posteriors the implantation of the energy efficiency project. From the measurements of electric energy and of solar irradiation data, this latters provided by the National Institute of Meteorology (INMET), it was possible to determine the performance ratio, the yield and the capacity factor of the SFVCR of Central Headquarters. Were also carried out consumption measurements of the lighting circuits, first with ordinary lamps and then with led lamps, being considered equal periods of consumption for the two types of lamps, respectively. At the end of the present, it was possible to compare the total consumptions of electric energy of Headquarters Central, before and after the execution of the energy efficiency actions at headquarters, which made it possible to establish the amount of energy saved in the period considered.